2015
DOI: 10.1007/s10856-015-5596-y
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of adhesive proteins to the cellular and bacterial response to surfaces treated with bioactive polymers: case of poly(sodium styrene sulfonate) grafted titanium surfaces

Abstract: The research developed on functionalized model or prosthetic surfaces with bioactive polymers has raised the possibility to modulate and/or control the biological in vitro and in vivo responses to synthetic biomaterials. The mechanisms underlying the bioactivity exhibited by sulfonated groups on surfaces involves both selective adsorption and conformational changes of adsorbed proteins. Indeed, surfaces functionalized by grafting poly(sodium styrene sulfonate) [poly(NaSS)] modulate the cellular and bacterial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The "grafting from" approach (Scheme 1) has attracted considerable attention in recent years for the preparation of tethered polymers onto a solid substrate surface [106]. The direct grafting of an ionic polymer model such as poly(sodium styrene sulfonate (polyNaSS) (Scheme 1) in a two-step reaction procedure onto titanium and alloy titanium surfaces was reported [106][107][108][109][110][111][112][113]. Treatment of the titanium surface by a mixture of sulfuric acid and hydrogen peroxide generates titanium hydroxide and titanium peroxide.…”
Section: Grafting Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The "grafting from" approach (Scheme 1) has attracted considerable attention in recent years for the preparation of tethered polymers onto a solid substrate surface [106]. The direct grafting of an ionic polymer model such as poly(sodium styrene sulfonate (polyNaSS) (Scheme 1) in a two-step reaction procedure onto titanium and alloy titanium surfaces was reported [106][107][108][109][110][111][112][113]. Treatment of the titanium surface by a mixture of sulfuric acid and hydrogen peroxide generates titanium hydroxide and titanium peroxide.…”
Section: Grafting Frommentioning
confidence: 99%
“…In the second reaction step, heating or UV irradiation of surfaces, if the substrate is placed in a concentrated solution of sodium styrene sulfonate monomer (NaSS) monomer, induces the decomposition of titanium peroxides with the formation of radicals capable of initiating the polymerization of NaSS. [107][108][109][110][111][112][113] A great advantage of polyNaSS grafting relies on its bioactivity, which could partly be explained by its moderate hydrophilic character. A bacterial adhesion study showed that titanium and titanium alloy graft surfaces exhibited high inhibition of S. aureus adhesion at levels greater than 70% when compared to non-grafted titanium and titanium alloy surfaces.…”
Section: Grafting Frommentioning
confidence: 99%
“…Such modified titanium surfaces provide us a promising strategy for preventing biofilm-related infections and enhancing osteointegration of implants in dental applications [157], due to its osteoblastic selective nature by its sulphonate group [158,159] and the negative charge might be the reason for antibacterial property [160].…”
Section: Poly (Sodium Styrene Sulphonate) Groupsmentioning
confidence: 99%
“…27 Here, sulfonated monomers were included in the synthesis of nanoparticles to provide stable negative charges as proven by the zeta potential data throughout a wide pH range ( Figure 2C), similar to previous literature on improved colloidal stability of poly(styrenesulfonate)-coated nanoparticles assessed through sedimentation tests. 28 In contrast, the zeta potential of PBNP was close to zero in the pH range 7-7.5, in accordance with the aggregation tendency of PBNP in this pH range ( Figure 2B) or over storage (Figure 3).…”
Section: Figurementioning
confidence: 58%